Fathers at work: work-family conflict, work-family enrichment and parenting in an Australian cohort - Lucas, Nina; Cooklin, Amanda; Giallo, Rebecca; Strazdins, Lyndall; Nicholson, Jan; Westrupp, Elizabeth (My University, 2016)
Contemporary fathering is characterized by the combined responsibilities of employment and parenting. Relationships between work–family conflict, work–family enrichment, and fathering behaviors have not been widely investigated. Secondary data from fathers of 4- to 5-year-old children participating in the Longitudinal Study of Australian Children were analyzed (N = 2,679). Results revealed that higher work–family conflict was associated with irritable (β = .06, p < .001), less warm (β = −0.04, p < .01), inconsistent parenting (β = −.07, p < .001), when sociodemographic and child characteristics were controlled for. Protective associations were found between work–family enrichment and optimal parenting behaviors (β = .10 warmth; β = −.05 irritability, p < .01). These results were largely unchanged when mental health was included in analyses. Sole-earner fathers and those employed for long hours were most likely to report high work–family conflict. Findings provide impetus for workplace and public policy to extend optimal, family-friendly employment conditions to all parents, including fathers.
Journal of Family Issues
Keywords: Families -- Parents and Parenting; Stress -- Work / family balance; Families -- Fathers; Families and relationships; Stress; Families; Fathers; Work / family balance; Parents and Parenting; Families and relationships